Rancang Bangun Media Pembelajaran IPS Berbasis Google Sites Materi Proklamasi Kemerdekaan Indonesia - Yona Wahyuningsih; Vian Yulianty (Universitas Muhammadiyah Kuningan, 2023)
This research is motivated by optimizing the material for the proclamation of Indonesian independence in the fifth grade of elementary school in social studies learning -based media Google Sites. The use of technology in the use of learning media by teachers is one form of effort to achieve learning success. This research is a development research that develops media based Google Sites in social studies learning in fifth grade elementary school. The research method uses the D&D (Design & Development) method with research stages based on the ADDIE development model which consists of 5 stages, namely Analyze (Analysis), Design(Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). Data collection techniques using interviews and questionnaires. The results of the development of Google Sites get an